21‐2: Highly Reliable Amorphous Indium‐Gallium‐Zinc‐Tin‐Oxide TFTs with Back‐Channel‐Etch Structure. Issue 1 (May 2017) - Lu, Xin-Hong; Wang, Ke; Hu, Hehe; Zhang, Wenlin; Ning, Ce; Yang, Wei; Wang, Jiushi; Yao, Qi; Cao, Zhanfeng; Yuan, Guangcai; Huang, Yinglong
Abstract : Back‐channel‐etch‐structured thin‐film transistors (TFTs) employing amorphous Indium‐Gallium‐Zinc‐Tin‐Oxide (IGZTO) and Mo/Al as active layer and source/drain, respectively, were demonstrated with good electronic property and bias‐temperature‐stress stability. LCD panels addressed by such TFTs with gate‐driver‐on‐array circuit passed the 1000‐ hour high‐temperature‐operating and high‐temperature/humidity‐operating reliability tests, revealing excellent prospect for mass‐production.